Does Financial Risk Education Improve Financial Literacy? Evidence from a Quasi-Experimental Study among Indonesian University Students - Bulan Nettiary Kelara; Tika Rahma Yani Siregar (JURNAL ECONOMINA, 2026)
The rapid expansion of digital financial services has increased the importance of financial literacy, particularly among young adults who are increasingly exposed to consumer credit products, online lending, and buy-now-pay-later services. This study aims to evaluate the effectiveness of a financial risk education program in improving financial literacy among Indonesian university students. A quantitative approach employing a one-group pretest-posttest quasi-experimental design was used. The study involved 70 undergraduate students from the Faculty of Economics, Universitas Sriwijaya, who participated in a financial risk education program covering financial literacy, consumer financing, responsible borrowing behavior, digital financial services, and financial risk management. Data were collected through structured questionnaires administered before and after the intervention and analyzed using the Wilcoxon Signed-Rank Test. The findings revealed a significant improvement in participants’ financial literacy following the intervention, with the mean score increasing from 30.04 to 30.94. The Wilcoxon test indicated a statistically significant difference between pretest and posttest scores (Z = 2.151; p = 0.0315). Furthermore, participants demonstrated a high level of understanding regarding responsible borrowing, the risks associated with excessive use of paylater services, and impulsive buying behavior. These findings suggest that financial risk education can serve as an effective strategy for enhancing financial literacy and promoting more responsible financial decision-making among university students.